Isolation, characterization and adhesion performance of sorghum, canola and camelina proteins - Li, Ningbo (Kansas State University, 2014)
Sorghum distillers dried grains with solubles (DDGS), canola and camelina meals are the main co-products resulting from grain-based ethanol or oil production. The main objective of this research was to study physicochemical properties of proteins isolated from DDGS, canola and camelina meals and their adhesion performance. Acetic acid-extracted sorghum protein (PI) from DDGS had superior adhesion performance in terms of dry, wet and soak adhesion strength compared to acetic acid-extracted sorghum protein (PF) from sorghum flour and aqueous ethanol-extracted sorghum protein (PII) from DDGS. PI had a significantly higher wet strength (3.15 MPa) than PII (2.17 MPa), PF (2.59 MPa), and soy protein without modification (1.63 MPa). The high content of hydrophobic amino acids in PI (57%) was likely the key factor responsible for high water resistance. Canola protein was extracted from canola meal and modified with different concentrations of NaHSO3 (0 to 15 g/L) during protein isolation. Unmodified canola protein showed the highest wet shear strength of 3.97 MPa cured at 190 °C. Adhesion strength of canola protein fractions extracted at pH 5.5 and pH 3.5 (3.9-4.1 MPa) was higher than the fraction extracted at pH 7.0. NaHSO3 slightly weakened adhesion performance of canola protein; however, it improved handling and flow-ability due to breaking of disulfide bonds in proteins. Albumin, globulin, and glutelins were isolated from camelina meal. Adhesion performance of globulin fraction behaved better than glutelin fraction. The greatest wet shear strength of globulin was 3.3 MPa at curing a temperature of 190 °C. Glutelin had a more protein aggregation compared with globulin, as indicated by higher crystallinity and thermal stability, and dense protein aggregate. This compact structure of glutelins may partially contribute to lower adhesion strength as compared to globulin.
Keywords: Sorghum protein; Camelina protein; Protein isolation; Canola protein; Protein based adhesion; Protein properties; Agriculture, General (0473)